Fundamentals of Anatomy and Physiology - Chruścik, Anna; Kauter, Kate; Whiteside, Eliza; Windus, Louisa (Open textbook library., 2021)
The University of Southern Queensland (USQ) is committed to advancing the use of open textbooks in higher education. This textbook is a tool to support first year anatomy and physiology courses taught in Australia, aiming to provide students with an increased access to free, high-quality learning materials. The material in this textbook is largely based on OpenStax’s Anatomy & Physiology textbook, however, has been modified for Australian course curriculum.